STRATEGI GURU DALAM MENUMBUHKAN MINAT BACA ANAK MELALUI MEDIA KARTU GAMBAR DI SEKOLAH - Yuli Rahma Sari; Dita Widiyanti (Jurnal Al Athfaal, 2023)
The purpose of this study is to document and analyze the experience and impact of using picture card technology to increase children's interest in reading. Descriptive qualitative research allows researchers to thoroughly understand how children engage and respond to this learning approach. As part of this study, several young children were provided with a learning environment enriched with picture cards. Data was collected through participant observation, interviews with teachers and children, and recording of learning activities.We then used a thematic coding process to identify patterns, themes and other key elements that emerged as children navigated their learning strategies. We then used a thematic coding process to identify patterns, themes and other key elements that emerged as children navigated their learning strategies. The research showed that picture cards made young children more interested in reading. Children's comprehension of stories increased, their creativity in connecting pictures and words increased, and their enthusiasm for reading activities increased. In addition, the results revealed qualitative elements in the learning process, such as the influence of social interaction between children and visual approaches on children's literacy development.